2014
DOI: 10.4236/wjcmp.2014.44024
|View full text |Cite
|
Sign up to set email alerts
|

Bright Red Luminescence and Structural Properties of Eu<sup>3+</sup> Ion Doped ZnO by Solution Combustion Technique

Abstract: Pure, and Europium ion doped Zinc oxide nanocrystals (ZnO:Eu 3+ ) were synthesized by a solution combustion technique. The X-ray diffraction patterns (XRD) reveals the existence of the Eu 2 O 3 phase. From the results of both, X-ray diffraction and photoluminescence spectra (PL) reveal that Eu 3+ ions successfully substitute for Zn 2+ ions in the ZnO lattice, moreover, when the amount of doped Europium was varied, this changes are showed in changes in the luminescence intensity. The PL is broad and a set of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The latter shoulder peak is broad and might be composed of several components in spite of the very good fit when using one peak component. This peak is sometimes also connected to defects, such as oxygen vacancies, showing a peak appearing in the lower-BE part of this oxygen peak. ,,,,,,,, ,, It might also contain a component of carboxylate or carbonate oxygen with a slightly higher BE of 531.6 eV, found for the Eu–oxo-carbonate, as indicated by its IR spectrum . Yet, a minor component of it could fit within the high-BE side of the broad 531.33 eV peak.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter shoulder peak is broad and might be composed of several components in spite of the very good fit when using one peak component. This peak is sometimes also connected to defects, such as oxygen vacancies, showing a peak appearing in the lower-BE part of this oxygen peak. ,,,,,,,, ,, It might also contain a component of carboxylate or carbonate oxygen with a slightly higher BE of 531.6 eV, found for the Eu–oxo-carbonate, as indicated by its IR spectrum . Yet, a minor component of it could fit within the high-BE side of the broad 531.33 eV peak.…”
Section: Resultsmentioning
confidence: 97%
“…In the Eu 3d region, the ZnO:5%Eu sample showed two sets of peaks around 1134 and 1164 eV, corresponding to photoemission from the Eu 3d 5/2 and Eu 3d 3/2 levels, respectively. , ,,,,,,,,,,, The Eu 3d 5/2 core level peaks can be seen as consisting of three groups with peak components at (i) 1124.30 (1.62) and 1126.44 (1.37), (ii) 1131.66 sh (6.38), 1134.34 (76.99), and 1136.84 sh (8.87), and (iii) 1142.87 (4.77) eV. Following the prevailing assignments in the literature, the first group of peak components on the low-energy side are associated with Eu 2+ , while the second group of peaks are associated with Eu 3+ . ,,, These BE values correspond well with the literature values for europium oxides. ,,,,,,,, ,, , The satellite peak at 1142.87 eV is associated with shake-down processes. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Figure 4(a) and Figure 4(b) shows the room temperature photoluminescence spectra (PL) of the Eu 3+ doped ZnO without the Cu 2+ ion dopant and of the Cu 2+ +Eu 3+ doped ZnO (ZnO:Cu 2+ +Eu 3+ ) nanocrystals as a function of the Cu 2+ ion concentration in Wt% and after both samples undoped and doped with the Cu 2+ were annealing at 900˚C by 24 h, the samples were irradiated with an excitation wavelength of 270 nm (in the UV range). In Figure 4(a) it is observed that the PL spectra correspond to the Eu 3+ ion emission in a ZnO matrix, in particular the most intense peak at the visible color red whit 613 nm in wavelength [27]. However it is observed from Figure 4(b) that the ZnO:Cu 2+ +Eu 3+ samples doped with 1, 2, 3, 10, and 20 Wt% are all alike: because they does not present antypical green broad emission band from 400 nm to 600 nm centered about 516 nm [28] as is showed in Figure 4(a), this band is due to the intrinsic defects emission of ZnO host.…”
Section: Photoluminescence Studymentioning
confidence: 98%
“…The introduction of Cu 2+ ions into ZnO lattice sums or produces changes that improve the ZnO properties such as: band gap tailored, magnetic and electrical properties, passivation of defects, as p-type dopant in the original n-type ZnO semiconductor. However, actually it is well known that the co-doping with Cu 2+ ion in Eu 3+ doped glasses photoluminescent compounds the Cu 2+ ion can quench the Eu 3+ photoluminescence [27]- [29] with the increase of the Cu 2+ ion concentration in glasses matrix; this quenching effect can be used to tuning between ultra-violet and visible emission in devise photoluminescent. In this study co-doped ZnO/Cu 2+ + Eu 3+ solid solution powders have been synthesized by solution combustion method as a function of the Cu 2+ ion concentration in %Wt.…”
Section: Introductionmentioning
confidence: 99%